2nd International Conference on Economics, Social, Management, Business (ICOESMB) - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2021)
Recently Professor Dr Nor Hashima Hashim from the Arshad Ayub Graduate Business School, UiTM was invited as a speaker for the 2nd International Conference on Economics, Social, Management, Business (ICOESMB) organised by the Fakultas Ekonomi Dan Bisnis Islam, Universitas Muhammadiyah Kendari, Sulawesi Tenggara, Indonesia. The conference was held on 7 August, 2021.